Samsung field lab voids: development of a data science application using agile methodology - Fleer, Jannis Marvin (2021)
VOIDS is a data science student entrepreneurial project that aims to integrate marketing into demand planning, helping companies to achieve the most accurate way of planning and shaping future demand. The following work applies this vision in a lean agile start-up framework, implementing state-of-the-art deep learning time series forecasting techniques in the business context of the global consumer electronic brand Samsung. The individual work discusses the development of a data analytics dashboard. It elaborates why an agile development methodology has been implemented and lays out the selection of the underlying development framework. Furthermore, the resulting application is demonstrated and explained.